Laparoscopic surgery by spontaneous rupture of the esophagus, a case report of treatment Boerhaave syndrome - Galliamov, Eduard A.; Semenyakin, Igor V.; Erin, Sergey A.; Kytirev, Evgeniy A.; Gololobov, Grigorii Y.; Burmistrov, Alexandr I. (International Surgery Journal, 2020)
Spontaneous rupture of the esophagus, Boerhaave syndrome, is a rare pathology and emergency condition for the patient. Patient, 63-year-old, on the 6th day of the disease falls into the clinic, where a Boerhaave syndrome was diagnosed. Laparoscopic surgery was performed. Sanitation and drainage of the mediastinum, suturing of the perforation hole were performed. After the operation, а positive response to treatment was observed. A group of authors believes that a minimally invasive approach to the treatment of spontaneous esophageal rupture is the alternative method for patients with severe somatic status and a small perforated opening of the esophagus.